DAMPAK NEGATIF GAME ONLINE FREE FIRE TERHADAP PERILAKU KOMUNIKASI ANAK PEMAIN GAME ONLINE FREE FIRE DI DUSUN BILE TEPUNG LOMBOK BARAT - Fathurrijal, Fathurrijal; Hamudani, Hamudani; Rahmawati, Endang; Ishanan, Ishanan; Abdillah, M. Zaki (Universitas Hamzanwadi, 2023)
Apart from being a medium of entertainment, online games can also be used as a medium of communication between players, because online games have communication features that allow players to interact, even though they are in different places. The intensity of the interaction of free-fire online game players, depending on the duration of the game, the longer the duration of the game they participate in, the potential for negative communication behavior to arise spontaneously. This study found that there was a negative impact of the free-fire online game on the negative behavior and forms of communication of children playing free-fire online games in Bile Tepung Hamlet, West Lombok.